Rawls explained : from fairness to Utopia - Voice, Paul, 1958- (Ideas explained series, 2011)
This book introduces the reader to the political theories of the American philosopher John Rawls. Rawls was arguably the most important political philosopher of the twentieth century. Barely a word of political philosophy is written today that is not indebted in some way, either directly or indirectly, to the philosophical paradigm that Rawls bequeathed. On his death at aged 81 in 2002 his obituaries, written by some of the leading figures in Western philosophy, placed him alongside John Locke and Immanuel Kant in the canon of Western political philosophers. His colleague, the philosopher Hila.